PNU‐74654 enhances the antiproliferative effects of 5‐FU in breast cancer and antagonizes thrombin‐induced cell growth via the Wnt pathway. Issue 8 (11th January 2019) - Rahmani, Farzad; Amerizadeh, Forouzan; Hassanian, Seyed Mahdi; Hashemzehi, Milad; Nasiri, Seyedeh‐Najibeh; Fiuji, Hamid; Ferns, Gordon A.; Khazaei, Majid; Avan, Amir
Abstract: The Wnt/β‐catenin pathway is one of the most common pathways dysregulated in breast cancer, and may, therefore, be a potential‐therapeutic target. We have investigated the effects of PNU‐74654 in breast cancer, as a Wnt/β‐catenin inhibitor, either alone or in combination with fluorouracil (5‐FU). PNU‐74654 suppressed cell growth at an IC 50 of 122 ± 0.4 μmol/L and synergistically enhanced the antiproliferative activity of gemcitabine by modulating the Wnt pathway. Using a 3D cell culture model, we found that the PNU‐74654 caused tumor shrinkage. It reduced the migration of MCF‐7 cells (by an 18% reduction in invasive behavior) after the treatment with PNU‐74654 through perturbation of E‐cadherin and MMP3/9. PNU‐74654/5‐FU combination enhanced the percentages of cells in S‐phase and significantly increased apoptosis. Moreover, our data showed that this agent was able to inhibit the growth of tumor in a xenograft model, although this effect was more pronounced in the animals treated with PNU‐74654 plus 5‐FU. These data show the ability of PNU‐74654 to specifically target Wnt pathway, interfere with cell proliferation, induce‐apoptosis, reduce‐migration, and synergistically interact with 5‐FU, supporting further studies on this novel therapeutic‐approach for breast cancer.